Serum metabolomic profiles in BALB/c mice induced by Babesia microti infection - Shen, Liang; Wang, Chunhua; Wang, Ruilin; Hu, Xue; Liao, Shiying; Liu, Wentong; Du, Aoling; Ji, Shengwei; Galon, Eloiza May; Li, Hang; Xuan, Xuenan; Xiao, Juan; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The protozoan parasite Babesia microti is the primary cause of human babesiosis. This parasite invades and multiplies inside red blood cells (RBCs), and infections differ significantly based on the age and immune competency of the host. The aim of this study was to investigate the use of serum metabolic profiling to identify systemic metabolic variations between B. microti-infected mice and noninfected controls. Methods A serum metabolomics analysis of BALB/c mice that had been intraperitoneally injected with 107B. microti-infected RBCs was performed. Serum samples from the early infected group (2 days postinfection), the acutely infected group (9 days postinfection), and the noninfected group were collected and evaluated using a liquid chromatography−mass spectrometry (LC−MS) platform. Principal component analysis (PCA), partial least squares discriminant analysis (PLS-DA), and orthogonal partial least squares discriminant analysis (OPLS-DA) identified metabolomic profiles that differentiated the B. microti-infected and noninfected groups. Results Our results confirm that the serum metabolome is significantly influenced by acute B. microti infection and show that infection results in dysregulation of metabolic pathways and perturbation of metabolites. Acutely infected mice displayed perturbations in metabolites associated with taurine and hypotaurine metabolism, histidine metabolism, and arachidonic acid metabolism. Taurocholic acid, anserine, and arachidonic acid may be potential candidates as serological biomarkers for diagnosing B. microti infection at the acute stage. These metabolites could be further examined for their role in disease complexity. Discussion Our findings demonstrate that the acute stage of B. microti infection induces abnormalities in the metabolites present in mouse serum and provide new insight into the mechanisms involved in systemic metabolic changes that occur during B. microti infection.